Multi-optimization of three kicks in rugby - Seo, K.; Kobayashi, O.; Murakami, M. (The Engineering of Sport 6, Volume 1 Developments for Sports, 2006)
What are the features of the optimal kicks in rugby? What is the best way to achieve satisfactory kicks? The objective of this paper is to provide the answers to these questions by optimizing the initial velocity and angular velocity vectors for three kinds of kick — the punted kick, the kick into touch and the kick for goal.